Catechin Isolates from Gambir (Uncaria gambir Roxb) Maintain Glucose Homeostasis in Diabetic Model Rat - Rita, Rauza Sukma; Yetti, Husna; Santoso, Putra; Afriani, Nita (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2024)
The prevalence of diabetes mellitus is rising globally. Oxidative stress, which can result from hyperglycemia in diabetes, might have negative consequences. An antioxidant is needed to prevent hyperglycemia. Cathechin isolates are derived from gambir, which has many antioxidants. This study examines catechin isolates from gambir (Uncaria gambir Roxb.) effect on glucose homeostasis in rats induced by alloxan. For this experiment, 35 male rats were employed. Male rats were given alloxan (150 mg/BW, IP), and after 72 hours, blood glucose levels were assessed. If blood glucose levels exceeded 200 mg/dl, three oral catechin isolates were administered (T1=10 mg/kg/day, T2=20 mg/kg/day, and T3=40 mg/kg/day). Following blood collection on the experiment's last day, fasting blood glucose, glucagon and insulin levels were measured. Catechin isolates decreased blood glucose levels in all treatment groups compared to the positive control group (T1 = 150.750 ± 14.359 mg/dl; T2 = 159.750 ± 15.434 mg/dl, and T3 = 153.375 ± 20.207 mg/dl vs 385 ± 60.989 mg/dl) significantly (p value-0.05). A decrease in glucagon serum level was also observed in the treatment group vs positive control (T1: 193.855 ± 36.009 pg/ml, T2 = 286.689 ± 20.313 pg/ml, and T3 = 319.462 ± 30.060 pg/ml vs 529.825 ± 74.279 pg/ml), significantly. Catechine isolates in the T3 group showed an increase in insulin serum level compared to the positive control group significantly (T3 = 216.640 ± 38.230 µIU/ml vs 69.833 ± 3.071 µIU/ml). In conclusion, catechin isolates from gambir decreased blood glucose levels by reducing glucagon and increasing insulin serum levels.